Psychosocial Well-Being and Mental Health of Individuals in Marital and in Family Relationships in Pre- and Post-Genocide Rwanda - Mukashema, Immaculée (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XIII, 209 p. 1 illus.